Statement on the safety of EstroG‐100™ as a novel food pursuant to Regulation (EC) No 258/97 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA); Dominique Turck; Jean‐Louis Bresson; Barbara Burlingame; Tara Dean; Susan Fairweather‐Tait; Marina Heinonen; Karen Ildico Hirsch‐Ernst; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Monika Neuhäuser‐Berthold; et al. (EFSA Journal, 2017)
Abstract Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to update its scientific opinion on the safety of EstroG‐100™ as a novel food (NF) in the light of additional information submitted by the applicant. In its previous scientific opinion of 2016, the Panel concluded that EstroG‐100™, which is a hot‐water extract of a mixture of three herbal roots, is safe for the use in food supplements at the maximum intake level of 175 mg/day in post‐menopausal women, which is lower than the maximum intake level proposed by the applicant (514 mg/day). The Panel reached its conclusions based on the effects of EstroG‐100™ on liver and haematology as observed in several oral toxicity studies, the lack of information on liver and haematological parameters in human studies and the absence of chronic toxicity data. In view of the Panel's conclusion on the safety of EstroG‐100™, the applicant has now provided additional information on haematological and liver parameters for the human intervention study with EstroG‐100™ and historical control data related to the subchronic 90‐day oral toxicity study with EstroG‐100™. After assessing the additional information provided by the applicant, the Panel considers that the conclusion of the scientific opinion on the safety of EstroG‐100™ does not need to be revised, and thus, the Panel reconfirms that the NF is safe for the use in food supplements at the maximum intake level of 175 mg/day in post‐menopausal women.